Modelo ng Pagdadala: Lapit at Gamit (Burden Bearing Model: Approach and Application) - Distor, John Mark; Cardiño, Henmar (Social Sciences and Development Review, 2023)
This paper has the objective of exploring the appropriate and right approach and application of the Pagdadala Model of Dr. Edwin T. Decenteceo (1997, 1999) in the field of Filipino Psychology. Using Thematic Analysis, the researcher features highlighted themes from not more than twenty-seven articles based on different experiences, researches, and books. The seven highlighted themes are the following: (1) Application on Clinical Psychology; (2) Approach on Clinical Psychology; (3) Application and Approach on Industrial Psychology; (4) Application and Approach on Educational Psychology; (5) Application and Approach on Community; (6) Application on Psychological First Aid (PFA); and (7) Approach on Spirituality. The Pagdadala Model can be developed because this is based on the experiences of Filipinos and every individual has their own story of burden-bearing. Keywords: Filipino Psychology, Pagdadala Model, approach, application, burden-bearing